Roamers: Audiences on the Move Across Entertainment Platforms In Southeast Asia. Issue 1 (2nd January 2022) - Hill, Annette; Lee, Jian Chung
Abstract : Media industries recognise the extent to which the potential audiences for their products are now made up significantly of "roamers, " people finding diverse routes through the options available and combining them in different ways. The main research question in this article is: what sort of precise movements, combinations and connections become possible for roaming audiences in rapidly expanding commercial entertainment platforms? The article draws on emergent findings of a qualitative audience study in Malaysia and Indonesia, analysing patterns of movement across streaming services, e.g. Netflix, entertainment platforms, e.g. YouTube, and national cable and public television channels. Through empirical and theoretical research, we critically examine how the virtual and material are intertwined in audience mobility and motility. Through the use of visualisations of the media landscape by roamers, the trope of the "Netflix Park" signifies how motility is closely tied to media freedom and power. In our study, audiences adapt to life in a commodified culture; roamers combine global entertainment platforms and other piracy services, becoming enmeshed in the commercial foreclosure of new media spheres.